Pengembangan Jobsheet Electric Motor Control Training KIT dengan Pendekatan Saintifik - Sari, Widia; Krismadinata, Krismadinata (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research was carried out because, in the electric machine control practicum course, there was no valid, practical, and effective job sheet as a guide in using the electric motor control training KIT in the field of induction motor control studies. This research aims to develop a job sheet with a scientific approach where practitioners can actively achieve practice objectives through implementing 5M activities. The research method used is R&D research (research and development) using a 4D model consisting of define, design, develop, and disseminate stages. The subjects in this research were D3 students in electrical engineering, Faculty of Engineering, Padang State University. Based on the research result, validity value data was obtained from the three validator lecturers, each of whom stated that they were valid, so it can be concluded that the jobsheet developed was valid. The practicality test was carried out by a lecturer in the electrical engineering department and 9 students from D3 electrical engineering. The practicality questionnaire filled out by the lecturer in the subject concerned and students as respondents obtained very practical results. The effectiveness test was carried out by carrying out a practicum based on a scientific approach using the electric motor control training KIT in 3 meetings with different materials. From these three tests, it was stated that the resulting job sheet was valid, practical, and effective for use as a guide in using the electric motor control training KIT in the electrical machine control practicum course in the field of induction motor control studies.